2019
DOI: 10.1186/s12917-019-2139-7
|View full text |Cite
|
Sign up to set email alerts
|

Schmallenberg virus neutralising antibody responses in sheep

Abstract: BackgroundSchmallenberg virus (SBV) is a midge borne virus of cattle and sheep. Infection is typically asymptomatic in adult sheep but fetal infection during pregnancy can result in abortion, stillbirth, neurological disorders and malformations of variable severity in newborn animals. It was first identified in Germany and the Netherlands in 2011 and then circulated throughout Europe in 2012 and 2013. Circulation in subsequent years was low or non-existent until summer and autumn 2016, leading to an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Despite collection occurring during and after the 2016/2017 disease outbreak over a wide geographical area of Great Britain, 31 no SBV RNA was detected in ram semen at any stage. This does not completely eliminate the possibility that a small number of rams may shed viral RNA in semen.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Despite collection occurring during and after the 2016/2017 disease outbreak over a wide geographical area of Great Britain, 31 no SBV RNA was detected in ram semen at any stage. This does not completely eliminate the possibility that a small number of rams may shed viral RNA in semen.…”
Section: Discussionmentioning
confidence: 91%
“…These rams were also part of an SBV viral neutralising antibody study that found blood samples taken from 13 rams (seven semen samples in this study) displayed increases in antibody titres during October 2016. This suggested potential recent exposure to the virus during the 2016 breeding season, 31 yet no SBV RNA was detected in the semen of those rams. SBV has a relatively short viraemic period (2–6 days) 19 ; however, bulls that displayed seroconversion (2–4 weeks postinfection) also had consecutive positive SBV RNA in their seminal cell fraction, 20 eluding the testis as a potential privilege site for SBV infection and transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations